The Quadratic Reciprocity Law (A Collection of Classical Proofs) - Baumgart, Oswald (Springer, 2015)
This book contains a translation of Baumgart’s thesis Über das quadratische Reciprocitätsgesetz. Eine vergleichende Darstellung der Beweise (On the Quadratic Reciprocity Law. A Comparative Presentation of its Proofs) written in Göttingen a hundred years after Legendre’s publication of the reciprocity law. Its aim was to present and compare the proofs of the quadratic reciprocity law known to him in 1885. The introduction to this book, which was to give a detailed history of the number theory leading up to the statement and the first proofs of the quadratic reciprocity law, eventually evolved into a book of its own and will be published separately....